2006
DOI: 10.1111/j.1464-5491.2006.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome in an Arab population: a first look at the new International Diabetes Federation criteria

Abstract: The increased prevalence using the IDF criteria compared with the 1999 WHO criteria and the 2001 NCEP ATPIII definitions is striking and has huge implications for public health worldwide. The major reason for the higher rate using the new definition seems to be the predominant focus placed on central obesity. Using tighter criteria for fasting glycaemia has also played a factor. The question remains as yet unanswered as to whether the new IDF criteria are better at predicting hard outcomes such as diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 9 publications
11
55
3
Order By: Relevance
“…These results confirmed previous findings in Tunisian population [5][6][7]17 as well as in others population [18][19][20][21] . Sedentary lifestyle, the lack of participation in physical activities among adult Tunisian women, hormonal factors and postmenopausal weight gain may prove the large waist circumference in women 22,23 .…”
Section: Discussionsupporting
confidence: 82%
“…These results confirmed previous findings in Tunisian population [5][6][7]17 as well as in others population [18][19][20][21] . Sedentary lifestyle, the lack of participation in physical activities among adult Tunisian women, hormonal factors and postmenopausal weight gain may prove the large waist circumference in women 22,23 .…”
Section: Discussionsupporting
confidence: 82%
“…The MetS prevalence estimated in the current study is similar to that reported in a previous study carried out in a population of Greater Tunis, located in the north of Tunisia (10) . Several studies have reported an increased rate of MetS in women compared with men (8,10,21,22) . In the present study the higher MetS prevalence in women could be explained by the fact that central obesity was three times more frequent in women than in men (65?5 % v. 20?6 %, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, the prevalence of CMS syndrome (ATP criteria) did not differ between urban (33.8%) and rural (33.9%) population, while it did between adult males (28%) and females (39.6%) [28].…”
Section: Middle East and North Africamentioning
confidence: 99%